Biocompatibility study of curcumin-loaded Pluronic F127 nanoformulation (NanoCUR) against the embryonic development of zebrafish (Danio rerio) - Abdullah, Siti Nur Sharmila; Subramaniam, Kalai Arasu; Muhamad Zamani, Zahir Haizat; Sarchio, Seri Narti Edayu; Md Yasin, Faizah; Shamsi, Suhaili (MDPI, 2022)
Curcumin (CUR) has been studied for its biomedical applications due to its active biological properties. However, CUR has limitations such as poor solubility, low bioavailability, and rapid degradation. Thus, CUR was nanoformulated with the application of polymeric micelle. Previous studies of CUR-loaded Pluronic F127 nanoformulation (NanoCUR) were generally prioritized toward cancer cells and its therapeutic values. There are reports that emphasize the toxicity of CUR, but reports on the toxicity of NanoCUR on embryonic developmental stages is still scarce. The present study aims to investigate the toxicity effects of NanoCUR on the embryonic development of zebrafish (Danio rerio). NanoCUR was synthesized via thin film hydration method and then characterized using DLS, UV-Vis, FTIR, FESEM, and XRD. The toxicity assessment of NanoCUR was conducted using zebrafish embryos, in comparison to native CUR, as well as Pluronic F127 (PF) as the controls, and ROS assay was further carried out. It was revealed that NanoCUR showed an improved toxicity profile compared to native CUR. NanoCUR displayed a delayed toxicity response and showed a concentration- and time-dependent toxicity response. NanoCUR was also observed to generate a significantly low reactive oxygen species (ROS) compared to native CUR in ROS assay. Overall, the results obtained highlight the potential of NanoCUR to be developed in clinical settings due to its improved toxicity profile compared to CUR.